Evaluating a nursing erasmus exchange experience: Reflections on the use and value of the Nominal Group Technique for evaluation. (September 2017) - Cunningham, Sheila
Abstract: This paper discusses the use of Nominal Group Technique (NGT) for European nursing exchange evaluation at one university. The NGT is a semi-quantitative evaluation method derived from the Delphi method popular in the 1970s and 1980s. The NGT was modified from the traditional version retaining the structured cycles and but adding a broader group discussion. The NGT had been used for 2 successive years but required analysis and evaluation itself for credibility and 'fit' for purpose which is presented here. It aimed to explore nursing students' exchange experiences and aid programme development futures exchanges and closure from exchange. Results varied for the cohorts and students as participants enthusiastically engaged generating ample data which they ranked and categorised collectively. Evaluation of the NGT itself was two fold: by the programme team who considered purpose, audience, inclusivity, context and expertise. Secondly, students were asked for their thoughts using a graffiti board. Students avidly engaged with NGT but importantly also reported an effect from the process itself as an opportunity to reflect and share their experiences. The programme team concluded the NGT offered a credible evaluation tool which made use of authentic student voice and offered interactive group processes. Pedagogially, it enabled active reflection thus aiding reorientation back to the United Kingdom and awareness of 'transformative' consequences of their exchange experiences.